2015
DOI: 10.4103/0972-0707.153054
|View full text |Cite
|
Sign up to set email alerts
|

Biotoxicity of commonly used root canal sealers: A meta-analysis

Abstract: Introduction:The main objective of a root canal sealer is to provide a fluid tight seal. The purpose of this systematic meta-analysis was to determine the relative toxicity of commonly used root canal sealers like zinc oxide eugenol, calcium hydroxide, and resin-based sealers.Materials and Methods:An online search was conducted in peer-reviewed journals listed in PubMed, Cochrane, EBSCO, and IndMed databases between 2000 and 2012). Statistical analysis was carried out by using analysis of variance (ANOVA) foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 36 publications
0
35
0
3
Order By: Relevance
“…Sealapex™ after setting becomes unstable and disintegrated. [ 11 ] Its cytotoxicity is due to components such as isobutyl salicylates and polymethylene methyl salicylate resin[ 12 ] and Ca(OH) 2 itself because of its high pH. [ 12 ] Earlier studies have shown that Sealapex™ has longer setting time[ 13 ] and has proved to be cytotoxic even after 1, 7, and 14 days of evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Sealapex™ after setting becomes unstable and disintegrated. [ 11 ] Its cytotoxicity is due to components such as isobutyl salicylates and polymethylene methyl salicylate resin[ 12 ] and Ca(OH) 2 itself because of its high pH. [ 12 ] Earlier studies have shown that Sealapex™ has longer setting time[ 13 ] and has proved to be cytotoxic even after 1, 7, and 14 days of evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The main functions of root canal sealers are (i) sealing off of voids, patent accessory canals, and multiple foramina, (ii) forming a bond between the core of the filling material and the root canal wall, and (iii) acting as a lubricant while facilitating the placement of the filling core and entombing any remaining bacteria [ 1 ]. Due to the relative biological and technical importance of sealers, their chemical and physical properties have been the subject of considerable attention since their initial development in the early twentieth century [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…During root canal treatment, the infected tissues are removed, and the root canal system is shaped, disinfected, and sealed with a core bio-inert material (e.g., gutta percha) combined with an endodontic sealer. 4 The elimination of infection within the canal is crucial for the success of a root canal treatment, which is currently carried out through a variety of chemo-mechanical techniques. 5,6 Due to the complicated anatomical structure of the tooth root, it is well known that the complete eradication of the bacteria in the canal and dentin tubules is virtually impossible, regardless of instrumentation and irrigation procedures.…”
Section: Introductionmentioning
confidence: 99%